Studi Kualitatif Perilaku Pencegahan Deman Berdarah pada Rumah Tangga - Ishak Ishak (Universitas 'Aisyiyah Yogyakarta, 2018)
Based on the data of Pangkajene Health Care Center, Maritengngae, Sidenreng Rappang 2016, the number of dengue patients treated in 2013 as many as 50 patients, in 2014 decreased by 22 patients with the death of 2 patients, while in 2015 decreased by 15 patients. From the number of cases January 2013 to December 2015 as many as 87 patients. Puskesmas Pangkajene is the health center with the highest number of DHF patients in Sidrap district. This research is a qualitative study by using in-depth interview technique to informant (program manager from Puskesmas Pangkajene).